An Extravaganza Illustration of Mihály Zichy and Mikhail Vrubel: The Problem of the Visual Metaphor - Evgeny Pavlovich Alexeyev; Andrey Nikolayevich Merezhnikov (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2015)
The authors analyze a component of M. Vrubel’s artistic method. Using the term extravaganza illustration put forward by Yu. Gerchuk, the authors focus on M. Zichy’s role in the development of the theme of Lermontov’s The Demon. They state that for the contemporaries, Zhichy’s works were more preferable than the ones created at a later time by Vrubel that were taken as impossible and preposterous. Zichy’s Tamara’s Dance was a composition source of Vrubel’s illustration. A comparative analysis of Tamara’s Dance by both artists reveals the peculiarities of their understanding of images and metaphors employed by visual art. Zichy’s extravaganza illustration focuses on the illustrative metaphor and aims at making it more pronounced which means a strong and stable connection between the visual and verbal components. Vrubel creates a construction causing a series metaphors to emerge, and each of them may be regarded as material for one whole project.